Demographic analysis of online grocery shopping during the COVID-19 pandemic: a theoretical perspective with an expanded technology acceptance model - Ali AbdulHussein; Stanko Dimitrov; Brian Cozzarin (Cogent Business & Management, 2024)
Grocery shopping is a necessity. The COVID-19 pandemic created unprecedented disruptions to all aspects of life including grocery shopping. Many households found it difficult to replace in-store shopping channels as governments enforced closures. The purpose of this study is to uncover how households in Canada responded to closures by switching to online shopping. This behavior change was not uneven. We analyze the demographic factors associated with the change in consumer behavior. Using recently published data by Statistics Canada, our empirical study found that a female consumer (Odds Ratio (OR) = 0.69) is less likely to have increased OGS activities after the start of the pandemic. On the other hand, a consumer that is employed (OR = 1.36), 25–44 years old (OR = 1.68), university-educated (OR = 1.21) consumer, with a higher household income (OR = 1.10) is more likely to have increased OGS activities. An immigrant consumer (OR = 0.73) is less likely to have increased OGS activities. Different consumers exhibit different preferences for shopping platforms. This understanding offers a deeper understanding of consumer behavior to marketers, researchers, and policymakers who seek to improve online shopping for certain groups.
Keywords: 650; Online grocery shopping; COVID-19; consumer behaviors; technology acceptance model (TAM3); perceived risk; perceived ease of use